Taube Klara - Spillner, Wolf (Klopp, 1990)
The death of his grandfather's pigeon and the search for the causes force 10-year-old Hannes to examine the relationships in three generations of his family.
Lizenzausg. des Kinderbuchverl., Berlin
Keywords: Kinderbuch; Young adult fiction; German; Haustaube; Mutter; Großmutter; Weihnachten; Versöhnung; Enkel; Generationskonflikt; Tötung; Erwachsene Tochter; Familie